ANALYSIS OF THE QUALITY OF PUBLIC SERVICES IN THE FIELD OF SUPERVISION AND CIVIL RECORDS IN THE LARGER FIELD - Neisya Khaera Cahyani; Taufik Purboyo; Emiraldo Win Pazqara (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
The research entitled Analysis of Public Service Quality in the Population and Civil Registry Office in Banyumas Regency. This study aims to explain and describe the Quality of Public Services at the Population and Civil Registry Office in Banyumas Regency. This research uses qualitative methods with a descriptive approach. The qualitative approach is expected to be able to produce an in-depth description of speech, writing and behavior as well as an emphasis on observable subjective aspects of the subjects themselves. In qualitative research the authors determined the informants in this study were purposive sampling techniques. This research uses the theory from Parasuraman (2001: 26) which puts forward the concept of service quality related to satisfaction determined by five elements commonly known as